2012
DOI: 10.1002/jcb.24151
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methylation of SERBP1 by protein arginine methyltransferase 1 affects cytoplasmic/nuclear distribution

Abstract: Protein arginine methylation regulates a broad array of cellular processes. SERBP1 implicated in tumor progression through its putative involvement in the plaminogen activator protease cascade, is an RNA-binding protein containing an RG-rich domain and an RGG box domain that might be methylated by protein arginine N-methyltransferases (PRMTs). Asymmetric dimethylarginine (aDMA) was detected in SERBP1 and an indirect methyltransferase inhibitor adenosine dialdehyde (AdOx) significantly reduced the methylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 22 publications
2
58
0
Order By: Relevance
“…In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2]. As many SGincorporated proteins are RNA-binding proteins and may be arginine-methylated [10], we analyzed whether SERBP1 interacts with these proteins.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2]. As many SGincorporated proteins are RNA-binding proteins and may be arginine-methylated [10], we analyzed whether SERBP1 interacts with these proteins.…”
Section: Resultsmentioning
confidence: 98%
“…We have shown that SERBP1 is arginine-methylated in the central RG and C-terminal RGG regions [2]. Protein arginine methylation of some SG-incorporated RNA-binding proteins has been shown to be critical for their cellular distribution, and may further affect their sorting to SGs [10].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations